A new micromechanical model of CNT-metal nanocomposites with random clustered distribution of CNTs (Fracture and Structural Integrity, 2015)
Uniform dispersion of carbon nanotubes (CNTs) is a key issue for utilization of their reinforcement potential in CNT-reinforced metal matrix nanocomposites (MMNCs). It was reported that CNT clusters often exist in MMNCs prepared by various techniques, which reduces the load transfer efficiency between the matrix and reinforcement. In this paper, a new micromechanical constitutive model of CNT-reinforced MMNCs is developed, which takes into account of the influences of CNT clusters and misorientations. The strength values of a CNT/Al nanocomposite predicted by the new model are compared first with experimental data for validation. Then, the developed model is applied to predict the size effect, temperature effect and strain rate effect of the nanocomposite in its overall elastoplastic response.
Keywords: Micromechanical modelling